Penerapan Syarat Formil Dan Materiil Dalam Sebuah Surat Dakwaan Yang Dinyatakan Obscuur Libel Serta Persesuaian Pertimbangan Hakim Mahkamah Agung Dalam Menerima Permohonan Kasasi Dalam Putusan MA Nomor - Wijayanti, Retno Putri (Sebelas Maret University, 2013)
The objective of this research are to analyze and answer the problems about the application of formal and material requirements in indictment letter which is obscuur libel in corruption case by the Makasar high court in renovation of central Maros market by Hj. Nurwati and to asses consideration used by supreme court judge in accepting cassation petition proposed by public prosecutor. The result of study shows that public prosecutor in proposing indictment letter correspond to formal and material requirement of indictment letter based on KUHP. Makasar high court in stating indictment letter which is obcuur and libel is not corresponding to 143 clause of KUHP. Cassation petition by public prosecutor to acquittal verdict from Makasar high court is accepted by Supreme Court. Consideration conformity done by Supreme Court corresponds to KUHAP. This conformity consists of Makasar high court verdict which is contradictive each other, because there is wrong law application by Makasar high court, there is verdict beyond the limits of authority judex factie, and there is not accuracy of high court in judging which is not done based on law. Therefore the consideration of Supreme Court judge in accepting acquittal verdict of Makasar high court can be justified because there is not accuracy of high court judge in deciding case. Key words: obscuur libel indictment, cassation, corruption